For whom does the bell toll: a political analysis of criticisms of the Hawthorne studies. Issue 10 (18th May 2021) - Muldoon, Jeffrey; Liguori, Eric W.; Lovett, Steve; Stone, Christopher
Abstract : Purpose: This paper aims to analyze the political background of the Hawthorne criticisms, positing that the political atmosphere of the 1940s, influenced by the decline of the new deal liberalism and the rise of the conservative coalition, stimulated scholars to challenge the Hawthorne studies. Design/methodology/approach: Primary sources used in the guise of archival commentaries, journal articles and other published works (books and book chapters). Secondary sources are offered to provide additional insight and context. Findings: The findings show that politics unnecessarily discredited Mayo. As a result, contemporary scholars failed to recognize Mayo's work as an important part of the basis for modern management theory. Research limitations/implications: The purpose of the research is to look into the political context of the Hawthorne studies to understand how management practice and research is impacted by ongoing political issues. Originality/value: To date, no work has fully accounted for or understood the political climate of the time in considering the criticisms of the Hawthorne studies. By more fully understanding the political context, scholars can reevaluate the weight they place on the then criticisms of the Hawthorne studies.